2018
DOI: 10.1111/pce.13409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulsed UV‐B stress exposure on plant performance: How recovery periods stimulate secondary metabolism while reducing adaptive growth attenuation

Abstract: Upon continuous stress exposure, plants display attenuated metabolic stress responses due to regulatory feedback loops. Here, we have tested the hypothesis that pulsed stress exposure with intervening recovery periods should affect these feedback loops, thereby causing increased accumulation of stress-induced metabolites. The response of Arabidopsis plantlets to continuous UV-B exposure (C ) was compared with that of pulsed UV-B exposure (P ). The differential responses to P versus C were monitored at the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 70 publications
(97 reference statements)
0
24
0
Order By: Relevance
“…First, UVR8 dimer is converted to monomers by low-energy UV-B light, and the monomer then combines with CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1) to form a complex that stimulates ELONGATED HYPOCOTYL5 (HY5) transcription factor to activate stress defense responses. This leads to promote the biosynthesis of UV-B absorbing compounds, such as flavonoids, anthocyanins, and HCAs, which act as a sunscreen [ 9 , 10 , 35 , 36 , 37 , 38 ]. In addition, HY5 regulates a number of genes involving in the terpene biosynthesis pathway [ 39 ], and [ 40 , 41 ] reported that the relatively low UV-B radiation with 4.75 kJ d −1 induced the sesquiterpenes biosynthesis related to cell membrane stability, protecting leaves from UV-B-induced rapid heating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, UVR8 dimer is converted to monomers by low-energy UV-B light, and the monomer then combines with CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1) to form a complex that stimulates ELONGATED HYPOCOTYL5 (HY5) transcription factor to activate stress defense responses. This leads to promote the biosynthesis of UV-B absorbing compounds, such as flavonoids, anthocyanins, and HCAs, which act as a sunscreen [ 9 , 10 , 35 , 36 , 37 , 38 ]. In addition, HY5 regulates a number of genes involving in the terpene biosynthesis pathway [ 39 ], and [ 40 , 41 ] reported that the relatively low UV-B radiation with 4.75 kJ d −1 induced the sesquiterpenes biosynthesis related to cell membrane stability, protecting leaves from UV-B-induced rapid heating.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds synthesized via UVR8 pathway are involved in protective responses against environment-induced oxidative stress because of their high antioxidant capacity [ 35 , 36 , 37 , 38 , 42 ]. Secondly, ROS produced in chloroplasts, mitochondrias, and apoplasts due to high level of UV-B light generate ROS waves, which mediate rapid systemic signaling, activating ROS-scavenging pathway to stimulate the biosynthesis of antioxidant secondary metabolites [ 8 , 9 , 10 ]. If stress persists or stress level is high, the accumulation of ROS generated from these pathways will be greater than that of antioxidants level, which subsequently damages plants [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery periods between the stress events may support “training.” A study by Höll et al () compared the effects of pulsed UV‐B exposure on levels of plant metabolites involved in UV‐B protection with those of continuous UV‐B exposure. Although the total duration of pulsed and continuous UV‐B exposure was the same, plants experiencing the pulsed exposure accumulated more UV‐B‐protective flavonols.…”
Section: Priming By Transcriptional Regulation and “Training”mentioning
confidence: 99%
“…When allowed recovery periods, the capacity of plants to adapt to different stresses is enhanced when compared to continuous periods of stress ( Figure 6). In an experiment comparing constant doses of UV-B (6 h at 0.04 mW cm −2 ) and pulsed doses (6 × 1 h intervals interspersed with 30 min recovery periods), Arabidopsis plants allowed recovery periods produced more photoprotectants; 27% more total flavonols and sinapyl derivates, 38% more kaempferols, and 90% more quercetins (Höll et al, 2019). The authors also demonstrated that the amount by which these compounds increase depends on the duration of the recovery periods, with shorter recovery periods showing almost no differences when compared to plants treated continuously.…”
Section: Recovery Periodsmentioning
confidence: 99%